2015
DOI: 10.4028/www.scientific.net/amr.1112.205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fe<sub>3</sub>O<sub>4 </sub>Nanoparticles Using the Co-Precipitation Method and its Development into Nanofluids as a Catalyst in Aquathermolysis Reactions

Abstract: Catalytic aquathermolysis is proposed as one of the potential methods which functions to reduce the viscosity of heavy oil for ease of extraction. In this research, we have developed a solution dispersed catalyst of Fe3O4 nanoparticles through a co-precipitation method. FeCl3·6H2O and FeCl2·4H2O were used to serve as an Fe source, with NaOH as a co-precipitator. The as-synthesized nanoparticles were characterized by X-ray diffraction (XRD) to verify materials. In order to be able to be used in the reservoir, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The common preparation routes for spherical IONCs involve co-precipitation and thermal decomposition routes, which are well controlled during nucleation and growth processes. 28,29 In co-precipitation, without any surfactants, spherical IONCs are formed by homogeneous nucleation and isotropic growth, and formation of the final spherical NPs with low surface free energy is driven by kinetic factors during the growth process. However, the size distribution of these spherical IONCs is too broad, because of the broad distribution of supersaturation for nucleation and the crystal growth being only kinetically controlled.…”
Section: Xiangheng Xiaomentioning
confidence: 99%
“…The common preparation routes for spherical IONCs involve co-precipitation and thermal decomposition routes, which are well controlled during nucleation and growth processes. 28,29 In co-precipitation, without any surfactants, spherical IONCs are formed by homogeneous nucleation and isotropic growth, and formation of the final spherical NPs with low surface free energy is driven by kinetic factors during the growth process. However, the size distribution of these spherical IONCs is too broad, because of the broad distribution of supersaturation for nucleation and the crystal growth being only kinetically controlled.…”
Section: Xiangheng Xiaomentioning
confidence: 99%
“…Our preliminary work of water-based Fe 3 O 4 nanofluids preparation showed initial success in increasing the viscosity reduction of heavy oil compared to the use of nanoparticles (Iskandar F. et al, 2015). The result also reflected that the presence of surfactant under the addition of 20 wt% ethylene glycol had a negligible effect on catalytic performance degradation.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 80%
“…In this reaction, hematite was reduced at the initial reaction and then reoxidized by the presence of water . Meanwhile, another iron-based catalyst, namely, Fe 3 O 4 was also reported to upgrade heavy oil at 200 °C for 6 h. This study showed that viscosity of heavy oil reduced up to 71.3% …”
Section: Upgrading Heavy Oil Using Nanosized Oxidesmentioning
confidence: 94%
“…49 Meanwhile, another iron-based catalyst, namely, Fe 3 O 4 was also reported to upgrade heavy oil at 200 °C for 6 h. This study showed that viscosity of heavy oil reduced up to 71.3%. 50 Finally, a series of metal oxides consisting of NiO, Co 3 O 4 , and Fe 2 O 3 were studied by Nassar et al 51 as nanocatalysts for heavy oil upgrading. The average sizes of NiO, Co 3 O 4 , and Fe 2 O 3 were 12, 22, and 43 nm, respectively.…”
Section: Upgrading Heavy Oil Using Nanosizedmentioning
confidence: 99%